Managerial Skills for Micro, Small and Medium-sized Enterprises (MSMEs) - NG’ORA, Sebastian; MWAKALOBO, Adam Beni Swebe; LWESYA, Francis (Management Dynamics in the Knowledge Economy, 2022)
Effective managerial skills can play a key role in the internal governance of micro and small businesses in Africa, enabling them to survive, compete and thrive in a dynamic business environment. However, due to the low absorption capacity, many micro and small entrepreneurs and managers lack the necessary managerial skills. We collected data from MSMEs owners and managers in Tanzania to examine the managerial skills required and their effect on business performance based on thematic content analysis and regression analysis. The results show that the managerial skills of MSMEs owners and managers have a significantly positive effect on MSMEs performance, in particular, financial management, marketing, human relations, and entrepreneurial skills were crucial skills in running small businesses successfully. However, financial management, marketing and entrepreneurial skills were the main skills gaps for many MSMEs owners and managers, suggesting that education, mentoring, and training in these areas for MSMEs owners and managers need to be strengthened. This study argues that since young people form the majority of the stakeholders running small businesses, targeted policies and strategies to promote entrepreneurship among young people through entrepreneurial learning and experiences can help instil an entrepreneurial mindset, one of the crucial skills in small business management.